Correlation between Glasgow Coma Scale (GCS) Score and Lesion Location with Mortality in Patients with Ischemic Stroke - Pramesti, Neva Galih; Sulistyani, S; Busyra, B; Risanti, Erika Diana (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study evaluated the correlation between GCS scores and lesion locations with mortality in ischemic stroke patients. Methodology: This cross-sectional study analyzed secondary data from 50 ischemic stroke inpatients at RSUD dr. Soeratno Gemolong between August 2022 and August 2024. GCS scores were categorized as severe (≤8), moderate (9–12), and mild (13–15). Lesion locations were classified as supratentorial or infratentorial. The relationship between these variables and mortality was analyzed using the chi-square test. Results: A significant correlation was found between GCS scores and mortality (p = 0.001). Patients with severe GCS scores had a 54% mortality rate compared to 8% in patients with mild scores. No significant association was observed between lesion location and mortality (p = 0.118), although patients with supratentorial lesions showed a higher mortality rate (40%) than those with infratentorial lesions (28%). Applications/Originality/Value: GCS scores are a strong predictor of mortality in ischemic stroke patients, highlighting their importance in early risk stratification. Lesion location, while showing trends, was not significantly associated with mortality. The findings support healthcare policy improvements, personalized care, and future research into comprehensive stroke management. Further research is needed to explore these factors comprehensively and improve patient outcomes.